The Similarities and Differences of Kremlin’s Propaganda Matrix Used Against the Baltic States and Ukraine - Denisenko, Viktor (Žurnalistikos tyrimai, 2017)
In the article are analysed paradigms of Kremlin’s propaganda, used against the Baltic States and Ukraine. The research was made in a context of information warfare Russia implement against countries of the post-soviet area. The analysis of paradigms allows spotlight models of basic propaganda’s narratives – the matrix of propaganda. On the final stage of the research different matrix was compared. The main conclusion is that Kremlin uses similar strategies of propaganda against the Baltic States and Ukraine. In fact, first Kremlin’s propaganda matrix was formed after the collapse of Soviet Union and was used against Lithuania, Latvia and Estonia. Later comparable narratives were implemented against Ukraine (in the most powerful way during Maidan events and annexation of Crimea in 2014).
Keywords: ...